Preharvest calcium sprays improve fruit quality of 'Gala' apples in Southern Brazil - Amarante C.V.T.* (2002)
Calcium sprays have improved quality and storage life of apple fruits throughout the world. The efficacy of Ca sprays, however, varies according to soil, cultivar, and climatic conditions. This study has being carried out since 1998, in Southern Brazil, to evaluate the effect of calcium sprays on fruit quality of 'Gala' apples. Treatments consisted of 0, 4, 8, and 12 applications of 0.5% CaCl2 sprays. Fruits of same size and maturity level were analyzed for soluble solid content, titratable acidity, starch pattern index, flesh firmness, skin background color, russeting, physiological disorders, and for N, K, Ca and Mg, at harvest and after five months of cold storage at -1 °C and 90-95% RH. In the first two years, yield was greater than 45 t ha-1, fruits from all treatments were free of any disorder, and Ca sprays had no effect on-1 any leaf or fruit attribute. In the third season, however, when yield was 18 t ha-1, fruits did not develop any disorder at harvest, but, after storage, the incidence of bitter pit and lenticel blotch pit was inversely related to the number of Ca sprays, ranging from 25% with no calcium to 2% in the treatment with twelve calcium sprays. Averaged across years and treatments, the concentration of Ca in the fruits was 41 mg kg-1. It seems that the incidence of calcium related disorders in 'Gala' apples on high pH soils in Southern Brazil only occurs in seasons with light crop load as a result of large fruits and a high leaf/fruit ratio.